Behavioral Problems and Intervention Strategies Used by Teacher of Primary School in Chillan, Chile. - Vásquez Caballero, Cindy Verónica (2025)
Behavioral problems in the classroom have a negative impact on the emotional well-being of students, as well as on the learning process and classroom climate. This study aimed to describe the behavioral problems observed in the classroom, according to teachers' reports. A questionnaire created for this study was answered by 55 teachers, (female = 70,9% and men = 29,1%), among five schools of Chillán, Chile. Teachers indicated that among the behavioral problems, non-compliance behavior is observed with frequency (43,6%). This study is a starting point for future investigation on this topic, that addresses regional and national phenomena.